Dynamics of a vertical-flow windrow vermicomposting system - Hanc, Ales; Castkova, Tereza; Kuzel, Stanislav; Cajthaml, Tomas (Waste management & research, 2017)
Large-scale vermicomposting under outdoor conditions may differ from small-scale procedures in the laboratory. The present study evaluated changes in selected properties of a large-scale vertical-flow windrow vermicomposting system with continuous feeding with household biowaste. The windrow profile was divided into five layers of differing thickness and age after more than 12 months of vermicomposting. The top layer (0-30 cm, age <3 months) was characterised by partially decomposed organic matter with a high pH value and an elevated carbon/nitrogen (C/N) ratio. The earthworm biomass was 15 g kg-1 with a population density of 125 earthworms per kilogram predominantly found in clusters. The greatest amount of fungi (3.5 µg g-1 dw) and bacteria (62 µg g-1 dw) (expressed as phospholipid fatty acid analysis) was found in this layer. Thus, the top layer could be used for an additional cycle of windrow vermicomposting and for the preparation of aqueous extracts to protect plants against diseases. The lower layers (graduated by 30 cm and by 3 months of age) were mature as reflected by the low content of ammonia nitrogen, ratio of ammonia to nitrate nitrogen and dissolved organic carbon, and high ion-exchange capacity and its ratio to carbon. These layers were characterised by elevated values for electrical conductivity, total content of nutrients, available magnesium content, and a relatively large bacterial/fungal ratio. On the basis of the observed properties, the bottom layers were predetermined as effective fertilisers.
Keywords: odpadky - odstraňování; continuous feeding; biowaste; Composting; kompostování; Animals; půda; Soil; Large-scale windrow vermicomposting; Biodegradation, Environmental; earthworms; micro-organisms; Refuse Disposal; zvířata; Oligochaeta; biodegradace